2019
DOI: 10.3389/fgene.2019.01013
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Single-Nucleotide Polymorphisms in the Function of Candidate Tumor Suppressor ALDH1L1

Abstract: Folate (vitamin B9) is a common name for a group of coenzymes that function as carriers of chemical moieties called one-carbon groups in numerous biochemical reactions. The combination of these folate-dependent reactions constitutes one-carbon metabolism, the name synonymous to folate metabolism. Folate coenzymes and associated metabolic pathways are vital for cellular homeostasis due to their key roles in nucleic acid biosynthesis, DNA repair, methylation processes, amino acid biogenesis, and energy balance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 136 publications
(196 reference statements)
2
10
0
Order By: Relevance
“…18 ALDH1L1 gene expression is down-regulated in cancer, and low ALDH1L1 expression is associated with the occurrence and malignant expression of tumors. [44][45][46] In this study, we observed that ALDH1L1 rs2002287 was not associated with the overall risk of BC, while, in the subgroup analysis, we observed that PR-positive women who carried the C allele have a higher risk of BC, which is consistent with a previous report. 47 However, a conflicting conclusion was reported that rs2002287 was associated with a decreased risk of BC, 44 which may be attributed to the fact that the effect of SNP on cancer has racial specificity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…18 ALDH1L1 gene expression is down-regulated in cancer, and low ALDH1L1 expression is associated with the occurrence and malignant expression of tumors. [44][45][46] In this study, we observed that ALDH1L1 rs2002287 was not associated with the overall risk of BC, while, in the subgroup analysis, we observed that PR-positive women who carried the C allele have a higher risk of BC, which is consistent with a previous report. 47 However, a conflicting conclusion was reported that rs2002287 was associated with a decreased risk of BC, 44 which may be attributed to the fact that the effect of SNP on cancer has racial specificity.…”
Section: Discussionsupporting
confidence: 92%
“…[44][45][46] In this study, we observed that ALDH1L1 rs2002287 was not associated with the overall risk of BC, while, in the subgroup analysis, we observed that PR-positive women who carried the C allele have a higher risk of BC, which is consistent with a previous report. 47 However, a conflicting conclusion was reported that rs2002287 was associated with a decreased risk of BC, 44 which may be attributed to the fact that the effect of SNP on cancer has racial specificity. 48 At the same time, this is the first study on the relationship between rs2002287 and BC risk in Chinese people, so large sample sized case-control studies are needed.…”
Section: Discussionsupporting
confidence: 92%
“…78 Although ALDH1L1 is overexpressed in NSCLC and GC cancer, 79,80 ALDH1L1 is reported profoundly downregulated or silenced in cancers, rendering it a candidate tumor suppressor. 81,82 Nevertheless, ALDH1L2 is highly expressed and presents as an independent prognostic factor for overall survival in melanoma, PDAC, and CRC. 77,78,83 Depletion of ALDH1L2 markedly decreases the NADPH/NADP + and GSH/GSSG ratios, reduces the circulating tumor cells in blood and alleviates the metastatic burden.…”
Section: Pentose Phosphate Pathwaymentioning
confidence: 99%
“…In studies involving East Asian populations, the presence of genetic polymorphisms in ADH1B (rs1229984) and ALDH2 (rs671), as well as alcohol consumption, individually or in combination [13], increase the risk of breast cancer [36], HNC [17], and esophageal cancer [18,35]. Moreover, research has shown that alcohol consumption affects two major folate-metabolizing enzymes, ALDH1L1 and ALDH1L2, with a possible synergistic effect on carcinogenesis [37,38]. In this study, SNPs rs671 located on ALDH2 and rs10778364 located on ALDH1L2 were significantly associated with an increased risk for NPC, with or without alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%